Generative AI in Finnish SMEs: Exploring the opportunities and challenges in digital marketing - Ilonen, Matias (2025)
Content, such as blog texts or videos, made to satisfy the needs of the customer is seen as the key to successful marketing. As a new aspect to content marketing, in the early 2020s, artificial intelligence (AI), machine learning software and large language models (LLMs) are adopted on the organizational level. Generative AI (GenAI), such as OpenAI’s ChatGPT, is said to change the landscape of content marketing and personalization of content, as it is easy to use and can produce content faster than a human counterpart. GenAI can also help less resourceful organizations, such as small and medium-sized enterprises (SMEs) to boost their content marketing.